Деякі міфологічні елементи в турецьких народних піснях - Ф. Гюлай Мірзаоглу-Сиваджи (Народна творчість та етнографія, 2010)
One of the features of the folk song is that it is based on a symbolic expression. In Turkish folk songs many symbols are used, as in other cultures, and some of them have a mythological character. In this paper, Turkish folk songs will be analyzed in terms of mythological elements and the relationships between these symbols and mythological stories, motifs and symbols. Türkünün özelliği onun simgeleridir. Diğer kültürlerin gibi türkülerin de çok simgeleri var. Bazıları mitoloji nitelik taşımaktadır. Bu makalede türkülerin mitolojik unsurleri ve onların mitoloji hikayelerle, simgelerle ve motiflerle ilgisi incelenir.